Educational level, GDP & wages : a study on the direction of causality - Ang, Hock Yick (2012)
This paper examines the causal relationships between labour force education levels and real GDP per capita, as well as average real wages in Singapore from 1980 to 2009. As investment in education is generally costly and any potential benefits are not immediately realised or observable, it is of economic value to determine if investment in education yields positive returns; both at the macro level, in terms of economic growth, and at the micro level, in terms of wages. We begin with a preliminary analysis on the trends and correlation of these variables and follow up by conducting an empirical analysis on them. To determine the causal relationships, we employ the Granger causality test. The empirical results show evidence of positive unidirectional causality from labour force education levels to real GDP per capita and from average real wages to labour force education levels. Lastly, we discuss possible explanations for the results above.